2014
DOI: 10.7314/apjcp.2014.15.10.4251
|View full text |Cite
|
Sign up to set email alerts
|

Use of Blood Transfusion at the End of Life: Does it Have Any Effects on Survival of Cancer Patients?

Abstract: Background: Treatment of anemia is an important issue in the palliative care setting. Blood transfusion is generally used for this purpose in supportive care. However the place of blood transfusion in terminally ill cancer cases is less far established. Objective: We aimed to outline the use of transfusions and to find the impact of blood transfusion on survival in patients with advanced cancer and very near to death. Design: Patients dying in 2010-2011 with advanced cancer were included in the study. We retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
1
27
2
Order By: Relevance
“…In Italy, within 30 days of death, 23% of patients with incurable cancer received PCT [6]. This was within the range of previous published results, 18-33% [9][10][11].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In Italy, within 30 days of death, 23% of patients with incurable cancer received PCT [6]. This was within the range of previous published results, 18-33% [9][10][11].…”
Section: Discussionsupporting
confidence: 84%
“…But this time frame of has been used in other published studies [6,7,9,11,12,23,[25][26][27][28]. Retrospective studies most always are criticized as the completeness of data often is suboptimal and depends totally on medical documentation without matched controls beside the limited information about patients that died outside the hospital.…”
Section: Limitationsmentioning
confidence: 99%
“…During data extraction, an additional six articles were excluded as they did not assess a transfusion‐related outcome. One additional study was included after screening the references of a review article, resulting in a total of 13 studies that were included in the final analysis of data …”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies did not include a comparison group that was not transfused, but reported median or mean survival of 42 days to 3 months after RBC transfusion . In one retrospective cohort of palliative oncology patients who died in hospital, those receiving RBC transfusion had a longer duration of their terminal hospitalization compared to those not transfused (median, 15 days vs. 8 days) . Four studies reported increased Hb values posttransfusion as at least one endpoint.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Causes include chronic inflammation, erythropoietin deficiency, bone marrow infiltration, bleeding, haematinic depletion and treatment effects.…”
Section: Introductionmentioning
confidence: 99%